2011
DOI: 10.1182/blood-2010-12-326736
|View full text |Cite
|
Sign up to set email alerts
|

Human T cells expressing affinity-matured TCR display accelerated responses but fail to recognize low density of MHC-peptide antigen

Abstract: We have tested whether affinity-matured TCRs that retain peptide specificity improve the ability of primary human CD8 ؉ T cells to mount antigen-specific responses. We found that TCR affinity correlated with the speed of T-cell responses. High affinity TCR-antigen interactions rapidly initiated T-cell responses, but low affinity TCR/antigen interactions required longer time periods to elicit the same responses. Within the "natural" affinity range, increased TCR-to-antigen affinity correlated with improved abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 41 publications
(50 reference statements)
7
81
2
Order By: Relevance
“…Studies performed over the last two decades have focused on empirically mapping the relationship between pMHC affinity and T-cell activation (5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A number of studies have reported an optimal pMHC affinity for T-cell activation, but other studies have failed to observe the optimum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed over the last two decades have focused on empirically mapping the relationship between pMHC affinity and T-cell activation (5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A number of studies have reported an optimal pMHC affinity for T-cell activation, but other studies have failed to observe the optimum.…”
mentioning
confidence: 99%
“…A specific example is the NY-ESO-1 cancer antigen, for which both high-affinity TCRs and CARs have been produced (26,27). The optimizing of these therapies has focused, in part, on trying to determine the optimal receptor affinity for clinical efficacy (20,22,(28)(29)(30); reviewed in ref. 31).…”
mentioning
confidence: 99%
“…More importantly, our results indicate that the requirement to artificially engineer CTL TCR for higher-affinity recognition of MHC-peptide complexes may not be as critical as previously considered. Indeed, in some settings, increasing TCR affinity can impair, rather than enhance, CTL activity (20)(21)(22). Although it seems counterintuitive, this is likely due to the reduced ability of high-affinity CTL to undergo serial triggering, where one MHC-peptide complex sequentially engages several TCR to achieve a critical activation threshold (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The group is also leading translational application of emerging nuclease reagents including TALENs for the generation of universal Tcells depleted of alloreactive T-cell receptors. Within University College London, Prof. Hans Stauss and Dr. Emma Morris have shown that TCR-redirected T-cells can function in vitro and in vivo targeting tumor or viral antigens supporting clinical trial activity 34,41,42 and also that modifications to TCR sequences or transfer of additional molecules can enhance TCR expression and in vivo T-cell function, 43,44 that clinical-grade gene-modified cell products can be generated, 45,46 and that tolerance to tumor-associated antigens may be overcome. 47 Moreover, the group has also shown that genetic engineering of HSCs can alter the specificity of developing T-cells 48 and, in collaboration with others, has shown that gene-modified antigen-specific Tregs have suppressive function in vivo.…”
Section: Preclinical Activitymentioning
confidence: 99%